Diagnostic value of survivin for malignant pleural effusion: a clinical study and meta-analysis - Tian, Panwen (e-Century Publishing Corporation, 2014)
Objective: To investigate the diagnostic accuracy of survivin for malignant pleural effusion (MPE). Methods: Pleural effusion samples were collected from 40 MPE patients and 45 non-MPE patients. Pleural levels of survivin were measured by ELISA. Literature search was performed in Pubmed and Embase to identify studies regarding the usefulness of survivin to diagnose MPE. Data were retrieved and the pooled sensitivity, specificity and other diagnostic indexes were calculated. The summary receiver operating characteristics (SROC) curve was used to determine the overall diagnostic accuracy. Results: The pleural levels of survivin were higher in MPE patients than non-MPE patients (844.17 ± 358.30 vs. 508.08 ± 169.58 pg/ml, P < 0.05), at a cut-off value of 683.2 pg/ml, the sensitivity and specificity were 57.50% and 88.89%, respectively. A total of six studies were included in present meta-analysis, the overall diagnostic estimates were: sensitivity 0.74 (95% CI: 0.59-0.85); specificity, 0.85 (95% CI: 0.79-0.89); positive likelihood ratio, 4.79 (95% CI: 3.48-6.61); negative likelihood ratio, 0.31 (95% CI: 0.19-0.50), and diagnostic odds ratio, 15.59 (95% CI: 7.69-31.61). The area under SROC curve was 0.86 (95% CI: 0.82-0.89). Conclusion: Our study confirms that the pleural survivin plays a role in the diagnosis of MPE. More studies at a large scale should be performed to validate our findings.